2014
DOI: 10.1159/000361077
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Atrophy Progression in Eyes with Age-Related Macular Degeneration: Role of Fundus Autofluorescence Patterns, Fellow Eye and Baseline Atrophy Area

Abstract: Background/Objective: To evaluate if fundus autofluorescence (FAF) patterns around geographic atrophy (GA) and the status of the fellow eye have an impact on GA progression. Methods: We included 54 eyes of 35 patients with GA. Areas of GA were quantified by RegionFinder software. Results: GA progression rates in eyes with a diffuse trickling pattern (median 1.42 mm2/year) were significantly higher than in normal eyes (median 0.22 mm2/year) and eyes with other diffuse FAF patterns (median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…48 The progression rate associated with the 'diffuse trickling' phenotype was also found to be statistically significantly higher when compared to 'other diffuse' patterns in several other studies. 49,50 Fleckenstein et al measured the median GA enlargement rate of the 'diffuse trickling' phenotype to be 2.90 mm 2 /year, 50 closely aligning with the findings of Holz et al 30 Batioglu et al, however, showed a progression rate in the 'diffuse trickling' phenotype of 1.42 mm 2 /year, higher than 'other diffuse' FAF patterns which were associated with a rate of 0.46 mm 2 / year. 49 Although showing the same pattern of prognostic information, this study's considerably slower progression rate may highlight the difficulties in ascertaining the qualitative subtleties of atrophy and between FAF phenotypes.…”
Section: Faf Phenotypessupporting
confidence: 52%
See 3 more Smart Citations
“…48 The progression rate associated with the 'diffuse trickling' phenotype was also found to be statistically significantly higher when compared to 'other diffuse' patterns in several other studies. 49,50 Fleckenstein et al measured the median GA enlargement rate of the 'diffuse trickling' phenotype to be 2.90 mm 2 /year, 50 closely aligning with the findings of Holz et al 30 Batioglu et al, however, showed a progression rate in the 'diffuse trickling' phenotype of 1.42 mm 2 /year, higher than 'other diffuse' FAF patterns which were associated with a rate of 0.46 mm 2 / year. 49 Although showing the same pattern of prognostic information, this study's considerably slower progression rate may highlight the difficulties in ascertaining the qualitative subtleties of atrophy and between FAF phenotypes.…”
Section: Faf Phenotypessupporting
confidence: 52%
“…The ‘patchy’ phenotype was associated with a faster progression rate than ‘focal’ but slower than both the ‘banded’ and ‘diffuse’ phenotypes . The progression rate associated with the ‘diffuse trickling’ phenotype was also found to be statistically significantly higher when compared to ‘other diffuse’ patterns in several other studies . Fleckenstein et al .…”
Section: Prognostic Indicators In Atrophic Amdmentioning
confidence: 79%
See 2 more Smart Citations
“…Among measurements taken from FAF images, high-risk factors with an impact on disease progression include rapid atrophy enlargement in patients with geographic atrophy; rapid atrophy enlargement in the fellow eye; large initial atrophy size; an area of increased fluorescence surrounding the geographic atrophy; and fluorescence pattern surrounding the area of atrophy. 9,10 …”
Section: Discussionmentioning
confidence: 99%